Exploring experiences of parents of children with special needs at school entry: A mixed methods approach - Siddiqua, Ayesha (My University, 2014)
Background: The transition from pre-school to kindergarten can be complex for children who need special assistance due to mental or physical disabilities (children with “special needs”). We used a longitudinal mixed-methods approach to explore parents’ experiences with service provision as their children transitioned to school. Methods: Parents (including one grandparent) of 37 children aged 4 to 6 years completed measures assessing their perceptions of and satisfaction with services, as well as their perceptions of the children’s behaviour. Teachers completed measures indicating children’s school readiness and school adjustment. Semi-structured interviews were conducted with parents to understand their experiences with services. Findings: Post-transition, parents reported lower perceptions of services and decreased satisfaction than pre-transition. Pre-transition perceptions of services and satisfaction with services were associated with some of the children’s outcomes important for school success. Socio-economic characteristics of parents did not predict change in their perceptions of services or satisfaction with services post-transition. The following themes emerged from the qualitative data: qualities of services and service providers, communication and information transfer, parent advocacy, uncertainty about services, and contrasts and contradictions in satisfaction. The qualitative findings indicate parents were both satisfied and concerned with aspects of the post-transition service provision. Conclusions: While the quantitative results suggested that parents’ experience with services became less positive after their children entered school, the qualitative findings illustrated the variability in parents’ experiences and components of service provision that require improvements to facilitate a successful school entry.
Keywords: Transition to school; Children with special needs; School entry; Mixed methods research